TECHNOLOGICAL PEDAGOGICAL CONTENT KNOWLEDGE SELF ASSESSMENT SCALE (TPACK-SAS) FOR PRE-SERVICE TEACHERS: DEVELOPMENT, VALIDITY AND RELIABILITY - Tezcan KARTAL; Büşra KARTAL; Gülşah ULUAY (International Journal of Eurasia Social Sciences, 2016)
TPACK has been a new issue of interest for the last decade. Koehler and Mishra (2005) suggested TPACK framework to address the knowledge needed for teachers to integrate technology in their classrooms. Self-reported scales are the most common measurement tools for TPACK. Surveys can inform about participants’ beliefs, views, attitudes, and dispositions that are the most effective on their decisions related to teach with or without technology. Most of the TPACK surveys have lack about reliability and validity. In this study, a valid and reliable survey called TPACK Self Assessment Scale (TPACK-SAS) was developed to identify pre-service teachers’ self-perceptions and self-assesments of their TPACK. The steps (item pool, expert review, item performance analyses, validity, reliability and factor analyses) suggested by DeVellis (2003) were followed in the scale development process. TPACK-SAS was administered to 754 preservice teachers. After the analyses process, it consisted of seven subdomains, similar with the original framework, and 67 items. Pre-service teachers were also asked whether they have their own computers or not, where they access internet, amount of time they spend using computers, proficiency of using computers and their intentions to use computers. The relationships between these variables and TPACK subdomain were investigated.